2014
DOI: 10.1016/j.bbamem.2014.05.023
|View full text |Cite
|
Sign up to set email alerts
|

The role of ceramide chain length distribution on the barrier properties of the skin lipid membranes

Abstract: The skin barrier function is provided by the stratum corneum (SC). The lipids in the SC are composed of three lipid classes: ceramides (CERs), cholesterol (CHOL) and free fatty acids (FFAs) which form two crystalline lamellar structures. In the present study, we investigate the effect of CER chain length distribution on the barrier properties of model lipid membranes mimicking the lipid composition and organization of SC. The membranes were prepared with either isolated pig CERs (PCERs) or synthetic CERs. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 39 publications
10
82
0
Order By: Relevance
“…The most important of such deviations are a high level of unsaturated fatty acids, shorter lipid chain lengths (Mojumdar et al, 2014;Thakoersing et al, 2013Thakoersing et al, , 2015 and an imbalance in the level of ceramide subclasses (Thakoersing et al, 2012). These changes in lipid composition are expected to contribute significantly to the impaired skin barrier of HSEs (Mojumdar et al, 2014). With respect to the bound lipid profile, this is similar to that of native human skin (Ponec et al, 2003) however, it must be stated that measurements of this profile have been conducted with a lower level of precision.…”
Section: Tab 1: Models For Dermal Absorptionmentioning
confidence: 85%
See 1 more Smart Citation
“…The most important of such deviations are a high level of unsaturated fatty acids, shorter lipid chain lengths (Mojumdar et al, 2014;Thakoersing et al, 2013Thakoersing et al, , 2015 and an imbalance in the level of ceramide subclasses (Thakoersing et al, 2012). These changes in lipid composition are expected to contribute significantly to the impaired skin barrier of HSEs (Mojumdar et al, 2014). With respect to the bound lipid profile, this is similar to that of native human skin (Ponec et al, 2003) however, it must be stated that measurements of this profile have been conducted with a lower level of precision.…”
Section: Tab 1: Models For Dermal Absorptionmentioning
confidence: 85%
“…Although all lipid classes present in native human skin are also present in HSEs, there is a deviation in free lipid composition and organization compared to native human skin. The most important of such deviations are a high level of unsaturated fatty acids, shorter lipid chain lengths (Mojumdar et al, 2014;Thakoersing et al, 2013Thakoersing et al, , 2015 and an imbalance in the level of ceramide subclasses (Thakoersing et al, 2012). These changes in lipid composition are expected to contribute significantly to the impaired skin barrier of HSEs (Mojumdar et al, 2014).…”
Section: Tab 1: Models For Dermal Absorptionmentioning
confidence: 99%
“…hexagonal and orthorhombic, respectively) [75]. In vivo and in vitro studies of diseased and healthy SC have also demonstrated a direct correlation between the lipid chain length and the packing density and repeat distance in the resulting lipid phases; the relative content of the different ceramides classes also influences the molecular organization of the lipid lamellae [76][77][78][79][80]. As another example, the geometry and content of the lipid phases in samples of identical composition prepared in the exact same way except for a difference in the equilibration temperature of only 10°C are radically different [81].…”
mentioning
confidence: 99%
“…Depending on their chain lengths and headgroup architectures, the ceramides and the free fatty acids may participate in the same or in separate OR lattices [34]. Reduction of the content of free fatty acids, shortening the chain lengths of both ceramides and fatty acids and mismatch between the lipid chain lengths inhibit the formation of OR [19,33,76,92,93]. Ceramide EOS was found to stabilize the OR phases [94].…”
mentioning
confidence: 99%
See 1 more Smart Citation